FANATISME IDENTITAS KOMUNAL SEBAGAI PEMICU KONFLIK SOSIAL (Studi pada Konflik Sosial Kao-Malifut, Halmahera Utara) - Zulkifli Hi. Saleh (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2020)
North Maluku is a province in Indonesia which has a very diverse socio-cultural diversity. This plurality is supposed to be the wealth of the region, but in fact it creates social disasters in the form of communal conflicts. The aim of this study is to identify the main causes of social conflict between the Kao and Makean communities in Malifut, North Halmahera. The method used is qualitative with a phenomenological approach. The data also comes from in-depth interviews and documents. From the data found in the field, then analyzed with a phenomenological approach to describe the data that became the research findings. The results showed that religion was used as a means of mobilizing disputes, moreover, the Malifut area was inhabited by two ethnic groups with different religions. In the end, conflicts using religious symbols were dominant and could not be avoided. In addition, the conflict in Malifut occurred due to social jealousy. The domination of the political economy of the Makian (immigrants) ethnicity over the Kao as an indigenous population. Where is the concern of the Kao community if the Makian ethnic group as immigrants will control the natural resources in their ancestral land.